The Macrophage-iNKT cells axis: macrophage survival and activation are modulated upon invariant NKT cell interaction - Loureiro, José Pedro Pereira (2019)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia